School Ecosystem Based on the Implementation of Pancasila Values and Diversity in SMAN 5 Palembang - Rosa, Yuni Hartati Eliya; Nawawi, Effendi (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2023)
Indonesia is a country with a diversity of cultures, languages, religions, beliefs, ethnicities, races and local wisdoms but has the same vision and goals in the view of Bhinneka Tunggal Ika. The application and appreciation of Pancasila values and diversity in the school ecosystem in an independent curriculum is the right step to produce students who have good morals and morals, are honest, responsible, respect the rights of others, work hard, and so on. This study aims to determine the implementation of the appreciation of Pancasila values and diversity in the school ecosystem at SMA Negeri 5 Palembang. The research method used in this research is descriptive qualitative. Collection techniques were used for direct observation of researchers at schools, interviews with teachers and documentation. The data analysis technique used is data reduction, data presentation, conclusion/verification. Based on the results of the study it was concluded that SMA Negeri 5 Palembang had implemented a school ecosystem based on the values of Pancasila and Bhinneka Tunggal Ika through symbols, signs, activities or activities to familiarize students in the school environment both in the school environment and in the school environment. class and outside the classroom which is in line with the goal of an Merdeka curriculum, which is to create lifelong learners with the character of the Pancasila Student Profile.